Pendampingan Desain dan Promosi Produk Flaux Chenille UMKM Gunung Perca di Kelurahan Tipes, Kecamatan Serengan, Surakarta - Taufik Murtono (Institut Seni Indonesia Surakarta, 2022)
MSMEs (micro, small, and medium-sized enterprises) are crucial to the national economy’s growth. Evidently, MSMEs were able to contribute to Indonesia’s economic recovery amid both the 1998 financial crisis and the Covid-19 epidemic that began in 2020. There is a large batik and clothing business in the Surakarta area and its surrounds. MSME actors have created patchwork attire using production waste in the shape of patchwork. MSMEs in Gunung Perca in Tipes Village, Serengan District, Surakarta, made one of the innovations in the application of patchwork. This MSME uses the faux chenille (fake caterpillar) technique to create patchwork wallets and purses. With this method, many layers of patchwork are combined with seams that create lanes that are equally spaced over the fabric’s surface. To disclose the layer beneath, the top layer of fabric’s surface is cut. This process results in a thick, silky cloth with a caterpillar-like texture. The objectives of this service program are to: 1) assist in the application of design principles to the faux chenille pattern, 2) assist the design of social media marketing. Some of the outcomes of the service program are: products with motifs based on design principles, product promotion through social media and exhibitions, draft of scientific journal manuscripts, and copyright registration.